Managing Curriculum Coherence in Dual Education Systems: A Qualitative Case Study of National and Islamic Boarding School Integration in Indonesia - Mutolib, Abdul; Pudjaningsih, Wiwik (Yayasan Pendidikan Bima Berilmu, 2026)
The expansion of hybrid education systems has intensified challenges in achieving curriculum coherence across multiple normative frameworks. This study aims to analyze how curriculum coherence is strategically managed in a dual education system integrating national and islamic boarding school curricula within an Indonesian junior secondary school. This research employs a qualitative single-case study design. Data were collected through semi-structured interviews, non-participant observations, and document analysis. Data were analyzed using a hybrid deductive–inductive thematic approach that integrates conceptual frameworks with empirical field findings. The findings reveal that curriculum integration is not an additive process but a distributed governance achievement enacted through three interdependent mechanisms: structural alignment (vision reframing, curriculum mapping, and time allocation design), relational coordination (cross-domain collaboration and contextual integration practices), and adaptive monitoring (integrated evaluation and feedback loops). Despite structured planning, coherence remains dynamic and requires continuous negotiation due to dual accountability pressures, coordination fatigue, and epistemological tensions. This study proposes a distributed coherence governance framework as an analytical lens for understanding complexity management in hybrid faith-based education systems.